2019
DOI: 10.1177/1932296818823538
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Glucose Trends From Continuous Glucose Monitoring: Friend or Foe in Clinical Decision Making?

Abstract: In this commentary, we briefly review the currently recommended approaches to interpretation and management of continuous glucose monitor (CGM) rate of change (ROC) trend arrows and discuss the inherent difficulty in incorporating practical recommendations for their application into routine clinical care. We have limited our review and discussion to the currently available Dexcom G5 and G6 CGM systems and Abbott’s Freestyle Libre flash glucose monitor (FGM) system, as they are the most widely used and currentl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…This study also revealed that participants who wear CGM reported using less CHO to treat hypoglycemia, possibly due to earlier detection. Although there are mixed reviews of predictive trends using CGM arrows, 23 DCESs can work with PWD and their care partners to determine the amount of CHO they need based on sensor glucose, arrows, and alarms while considering the delay and personal variables. These findings support the need for better coverage and access to CGM in all PWD at risk for hypoglycemia.…”
Section: Discussionmentioning
confidence: 99%
“…This study also revealed that participants who wear CGM reported using less CHO to treat hypoglycemia, possibly due to earlier detection. Although there are mixed reviews of predictive trends using CGM arrows, 23 DCESs can work with PWD and their care partners to determine the amount of CHO they need based on sensor glucose, arrows, and alarms while considering the delay and personal variables. These findings support the need for better coverage and access to CGM in all PWD at risk for hypoglycemia.…”
Section: Discussionmentioning
confidence: 99%
“…57 While this is a significant advancement in diabetes technology, the approach to using trend arrows from flash CGM to make clinical decisions is not without concerns. 58,59 Therefore, some important caveats are necessary for the patient and pharmacist to understand prior to using, or recommending that treatment decisions be based on trend arrows. First, incorporation of trend arrow data to make treatment decisions from flash CGM has not been well studied in a controlled clinical trial.…”
Section: Methodsmentioning
confidence: 99%
“…First, incorporation of trend arrow data to make treatment decisions from flash CGM has not been well studied in a controlled clinical trial. 58 In a study conducted by Freckmann and colleagues which included a small number of subjects using a flash CGM device, trend indicators did a poor job of matching future glucose change, notably within the first few hours of carbohydrate intake and insulin administration. 60 The majority of ROC indicators were shown to overestimate glucose change, which could lead to hypoglycemia.…”
Section: Methodsmentioning
confidence: 99%
“…Change in bolus insulin dose according to trend arrows has been suggested for both patients with multiple daily injections and insulin pumps [ 2 ]. For users of insulin pump with the predictive low-glucose suspend (PLGS) feature, only the arrows for management of hyperglycemia (upward arrows) should be used for insulin adjustments, as the insulin pump algorithm has incorporated the downward arrows for hypoglycemia prevention [ 3 ].…”
Section: Introductionmentioning
confidence: 99%